HUBUNGAN ANTARA POPULASI MIKROORGANISME UDARA DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT DI SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH TERJUN MEDAN - Nin Suharti; Erman Munir; Dwi Suryanto; Harry Agusnar (Pascasarjana Universitas Negeri Medan, 2014)
Abstract. This study aims to determine the number of microorganisms in the landfill Terjun Medan and to determine its relationship with acute respiratory infections in the surrounding community. The results showed that at the center of TPAS (0 meter) the number of air microorganisms was 2322 cfu/m3. The farther from the center point the amount of air microorganisms declined with 94.4 % correlation rate. A safe distance was ≥ 750 meters, because the microorganism population was below the air quality standards established (<700 cfu/m3). Analysis of the incidence of acute respiratory infections in the community around landfill Terjun Medan indicated that the higher the population of air microorganisms the higher acute respiratory infections event with correlation value of 85.7 %. Identification of air microorganisms showed that the air around the landfill Terjun Medan contained acute respiratory infections causing microbes consisting of Streptococcus, Staphylococcus, Klebsiella, Corynebacterium, Aspergillus and Candida. Keywords : Landfill, Air Microorganisms, Acute Respiratory Infections